Mortality among children under the age of one: analysis of cases after discharge from maternity * - Elieni Paula dos Santos; Rosângela Aparecida Pimenta Ferrari; Maria Rita Bertolozzi; Alexandrina Aparecida Maciel Cardelli; Christine Bacarat de Godoy; Flávia Françoso Genovesi (SciELO, 2016)
Abstract OBJECTIVE To analyze infant death after discharge from maternity in the time period between 2000 and 2013. METHOD A cross-sectional retrospective quantitative study in a municipality northward in the state of Paraná. Data were analyzed using the SPSS®, and were subjected to Chi-square test, logistical regression, 95% confidence interval, and a significance level of p <0.05. RESULTS Two hundred forty-nine children were born, discharged from maternity and subsequently died; 10.1% in the neonatal period and 89.9% in the post-neonatal period. Pregnancy follow-up, birth, and child monitoring took place mainly in the public health system. There was a statistically significant association between the infant component and place of delivery (p =0.002; RR=1.143; IC95%=1.064-1.229), and a lower number of childcare medical visits (p =0.001; RR=1.294; IC95%=1.039-1.613). The causes of death in the neonatal period were perinatal conditions (40%); external causes (32%); and congenital malformations (20%). In the post-neonatal period, congenital malformations (29.9%), external causes (24.1%); and infectious-parasitic diseases (11.2%) were the causes of death. CONCLUSION Virtually all children were born in conditions of good vitality that were worsened due to potentially preventable diseases that led to death.